2021
DOI: 10.1097/j.pain.0000000000002218
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase-like 3 contributes to inflammatory pain by targeting TET1 in YTHDF2-dependent manner

Abstract: Relative mRNA level ** 0d 2h 1d 3d 7d Time after CFA injection Mettl14 0.0 0.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…At present, a large number of studies have shown that m 6 A modifications caused by the abnormal expression of m 6 A core modification and reading proteins are involved in various physiological and pathological processes, such as biological growth and development, sperm development and maturation, DNA damage repair, biological rhythms, and various types of tumors [ 33 , 46 ]. Chai et al showed that YTHDF2 could promote the malignant progression of gliomas by accelerating UBX domain protein 1 (UBXN1) mRNA degradation via METTL3-mediated m 6 A modification [ 1 ]; Pan et al verified that YTHDF2 could lead to the reduction of Tet1 mRNA decay by binding to m 6 A in Tet1 mRNA [ 47 ]; Hou et al confirmed that the small ubiquitin-related modifier (SUMO)ylation of YTHDF2 could significantly increase the binding affinity of m 6 A-modified mRNAs and subsequently result in deregulated gene expression responsible for cancer progression [ 48 ]. We speculated that METTL14 might repress ASS1 mRNA stability via an m 6 A-YTHDF2-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies have shown that m 6 A modifications caused by the abnormal expression of m 6 A core modification and reading proteins are involved in various physiological and pathological processes, such as biological growth and development, sperm development and maturation, DNA damage repair, biological rhythms, and various types of tumors [ 33 , 46 ]. Chai et al showed that YTHDF2 could promote the malignant progression of gliomas by accelerating UBX domain protein 1 (UBXN1) mRNA degradation via METTL3-mediated m 6 A modification [ 1 ]; Pan et al verified that YTHDF2 could lead to the reduction of Tet1 mRNA decay by binding to m 6 A in Tet1 mRNA [ 47 ]; Hou et al confirmed that the small ubiquitin-related modifier (SUMO)ylation of YTHDF2 could significantly increase the binding affinity of m 6 A-modified mRNAs and subsequently result in deregulated gene expression responsible for cancer progression [ 48 ]. We speculated that METTL14 might repress ASS1 mRNA stability via an m 6 A-YTHDF2-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and qRT-PCR. RNA extraction and qRT-PCR were performed as described previously (Pan et al, 2021). In brief, total RNA was extracted using RNAiso Plus protocol (catalog #9109, Takara) and reversely transcribed into cDNA using HiScriot II Reverse Transcriptase (catalog # R223-1, Vazyme).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory pain is evoked by inflammation-associated stimuli and is often established in animal models using wound incision or injection of inflammatory chemical irritants, such as complete Freund’s adjuvant (CFA), carrageenan or lipopolysaccharides (LPS) ( Pan et al, 2021 ). Recent literatures have demonstrated that intraplantar administration of complete Freund’s adjuvant (CFA) or ceramide not only down-regulates paw withdrawal mechanical threshold and paw withdrawal thermal latency, but also up-regulates the expression of the NOD-like receptor protein 2 (NLRP2)/caspase-1/IL-1β in small-sized DRG primary sensory neurons and the generation of NLRP3/caspase-1 in spinal dorsal horn neurons ( Matsuoka et al, 2019 ; Hua et al, 2022 ).…”
Section: Caspases and Inflammatory Painmentioning
confidence: 99%